Surgical management of a persistent periapical lesion using cone-beam computed tomography - Ziyad Allahem (Wolters Kluwer Medknow Publications, 2021)
Endodontic therapy has a high success rate. However, failed endodontic therapy with persistent periapical lesions may indicate the presence of an apical cyst that requires surgical apical intervention. The present case involved a 70-year-old woman who was referred after initiation of nonsurgical root canal treatment (NSRCT) in the upper left lateral incisor (tooth #22); due to recurrent swelling and sinus tract. Periapical radiographs showed an apical radiolucency on tooth #22. In a clinical examination, tooth #22 showed a normal response to cold and the electric pulp tester (EPT), while the upper left canine (tooth #23) showed a negative response to cold and the EPT. NSRCT was performed for tooth #23. Eighteen months later, the patient presented with the same chief complaint of recurrent swelling, and cone-beam computed tomography was performed to examine the extent of the apical lesion and plan for surgical intervention. Apical surgery was performed using a dental operating microscope. At the 18-month follow-up assessment, the patient's radiographs showed good bone healing and symptom resolution. This case report indicates that some cases with large persistent periapical lesions may require surgical intervention.